Effect of powdered activated carbon (PAC) concentration on locally developed hybrid membrane bioreactors (HMBRS) / L. Y. Wong and C. A. Ng - Wong, L. Y.; Ng, C. A. (2012)
Membrane bioreactor (MBR) system is recently a well-known process in purifying waste water into clean water. It is also a much safer disinfection treatment compared to the conventional water treatment plant. However, the fouling problems still a great challenge to be overcome for this system. This project aims to investigate the better condition for MBR in order to prolong the filtration progress. MBR was hybrid with powdered activated carbon (PAC) in different concentration, 0.1 g/L and 1 g/L. The investigation will include the relative performances of the hybrid MBRs during start up and approaching steady state as well as operation at a sludge retention time (SRT) of 30 days and infinity. Parameters used for comparison of the MBRs included mixed liquor suspended solids (MLSS), Chemical Oxygen Demand (COD) loads, EPS (extracellular polymeric substances), floc size, transmembrane pressure (TMP) (the key indicator of fouling) and filtration characteristics of the mixed liquor measured ex-situ. By identifying the optimum condition, the membrane can perform longer and better, which directly lower the operation cost in any of the application.